PERSEPSI SISWA TERHADAP PEMBELAJARAN TEKS ANEKDOT SECARA DARING - Zufli Achmad; Dewi Kusumaningsih; Sukarno Sukarno; Arum Puji Astuti (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
ABSTRACT The Covid-19 pandemic has disrupted the face-to-face learning process, therefore a solution is needed to answer these problems. Online learning (online) is an alternative that can overcome this problem. Online learning with online applications including Google classroom, Google from, Whatsapp groups and other media. Especially in language lessons in improving the making of anecdotal texts. The purpose of this study was to obtain a description of the effectiveness of the implementation of online learning at SMK Muhammadiyah 2 Sukoharjo in the creativity of writing anecdotal texts. This study used a survey method by distributing questionnaires conducted online, and the number of samples was 36 students in the TKR class X SMK Muhammadiyah 2 Sukoharjo study. Data were analyzed using quantitative descriptive techniques. The results of this study indicate that students are less effective and less understanding in online learning. The media used by students are gadgets (HP) and there are several obstacles faced during this online learning, ranging from technical problems when learning online, networking on gadgets, and quite expensive quota fees. Keywords: Online learning; effectiveness; constrains